Different Types of Anopheles Breeding Place in Low and High Malaria Case Areas (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Malaria is a disease which is transmitted through the bite of Anopheles mosquito. This study aimed to analyse the difference of type of Anopheles larva breeding places between low malaria case area, namely Mandor Village, and high malaria case area, namely North Amboyo Village, both in Landak Regency, West Kalimantan Province. The samples of Anopheles mosquito breeding places was acquired through accidental sampling from all Anopheles larva breeding places and spatial mapping of breeding place points. The data were analyzed using Chi-square test and Mann-whitney test. This study found 70 breeding place points which consisted of 8 types of place, namely dig well, drilled well, Illegal Gold Mining (PETI) well, puddle, fish pond, sewer, swamp, and rice field. The lowest larva density in Mandor Village was at PETI well (0.48/dip) and the highest was at dig well (0.75/dip). In North Amboyo Village, the lowest density was at number 3 dig well (0.2/dip) and the highest was at rice field (2.3/dip). It can be concluded that there was a significant difference of Anopheles breeding places between low and high malaria case areas.